Kepadatan populasi dan waktu efektif pelepasan tungau predator Neoseiulus longispinosus Evans untuk pengendalian Tetranychus kanzawai Kishida - Nhyra Kamala Putri; Ali Nurmansyah; Sugeng Santoso (Jurnal Entomologi Indonesia, 2021)
Kanzawa spider mite, Tetranychus kanzawai Kishida (Tetranychidae) is one of the most important pest mite in Indonesia. This mite is known as the pest of many crops, including cassava. Neoseiulus longispinosus Evans (Phytoseiidae) is a predatory mite commonly found on plant infested by kanzawa spider mite. This predatory mite has high potential to be developed as biological control agent of T. kanzawai. The aim of this research is to elucidate the effective density and release time of N. longispinosus to control T. kanzawai on cassava. The research was conducted in the greenhouse, using cassava of Mentega cultivar. T. kanzawai were introduced into the cassava plants two weeks after planting, with density 5 female adults/plants. N. longispinosus were introduced 1, 2, and 3 weeks after T. kanzawai introduction with predator:prey ratio of 0:5, 1:5, 2:5, dan 3:5, respectively. Population of T. kanzawai and N. longispinosus, and also plant damage were observed at 6 weeks after planting. N. longispinosus could suppress T. kanzawai population and the highest suppression occurred at the interaction between 3:5 ratio and the release time at one week after T. kanzawai infestation. There was no significant effect of N. longispinosus release at various release ratio and time on attack intensity of T. kanzawai.